The Impacts of the Covid-19 Pandemic on Passenger Railway Transportation - Arnaudov, Borislav (Research Papers, 2023)
The Covid-19 (coronavirus) pandemic upended the global economy. The pandemic has caused various economic and social changes in the world economy, and in particular in the organization of passenger railway transport. The most visible were the reductions in mobility in the transport sector in terms of global constraints, such as travel bans, quarantines, closures of various facilities and services, border restrictions, which led to a reduction in demand for transport services. The objective of the article is to analyze the effects of the pandemic on the passenger railway transport and outline the directions for increasing the competitiveness and resilience of transport in other future crises. The methodology used is based on statistical methods and comparative analysis in the research time period 2011-2021.